Ectopic expression of TaBG1 increases seed size and alters nutritional characteristics of the grain in wheat but does not lead to increased yields - Matthew J. Milner (BMC, 2021)
Abstract Background Grain size is thought to be a major component of yield in many plant species. Here we set out to understand if knowledge from other cereals such as rice could translate to increased yield gains in wheat and lead to increased nitrogen use efficiency. Previous findings that the overexpression of OsBG1 in rice increased yields while increasing seed size suggest translating gains from rice to other cereals may help to increase yields. Results The orthologous genes of OsBG1 were identified in wheat. One homoeologous wheat gene was cloned and overexpressed in wheat to understand its role in controlling seed size. Potential alteration in the nutritional profile of the grains were also analyzed in wheat overexpressing TaBG1. It was found that increased TaBG1-A expression could indeed lead to larger seed size but was linked to a reduction in seed number per plant leading to no significant overall increase in yield. Other important components of yield such as biomass or tillering did not change significantly with increased TaBG1-A expression. The nutritional profile of the grain was altered, with a significant decrease in the Zn levels in the grain associated with increased seed size, but Fe and Mn concentrations were unchanged. Protein content of the wheat grain also fell under moderate N fertilization levels but not under deficient or adequate levels of N. Conclusions TaBG1 does control seed size in wheat but increasing the seed size per se does not increase yield and may come at the cost of lower concentrations of essential elements as well as potentially lower protein content. Nevertheless, TaBG1 could be a useful target for further breeding efforts in combination with other genes for increased biomass.